How do Parents Perceive the Initial Medical Consultation on their Child’s Developmental Disorder? - Hotopp, Lena Charlott; Spindler, Ulrike Petra; Bach, Vivien Angela; Hornemann, Frauke; Syrbe, Steffen; Andreas, Anna; Merkenschlager, Andreas; Kiess, Wieland; Bernhard, Matthias K.; Bertsche, Thilo; Neininger, Martina Patrizia; Bertsche, Astrid (Klinische Pädiatrie, 2018)
Background A developmental disorder of a child has a major impact on the affected families’ lives. However, data about the parents’ perception of the revealing of the diagnosis is scarce.Patients and Methods Parents of children with developmental disorder treated as outpatients in a university hospital were interviewed about the initial medical consultation concerning the diagnosis of their child.Results Parents of 210 children agreed to take part in the study. 35/210 (17%) had to be excluded from the study as they were not able to remember the initial medical consultation, or claimed there was either no initial medical consultation or they did not attend it. The diagnosis of developmental disorder was made in median 4 months (Q25/Q75: 0/12; min/max: 0/63) after the parents had noticed the first symptoms. According to the parents, options to support the development of the child were the most frequently addressed topic in the initial medical consultation (119/175, 68%). Some parents wished more empathy (19/175, 11%), and less medical terminology (12/175, 7%). 114/175 (65%) of parents rated the initial medical consultation as “very good” or “good”. After their initial medical consultation, 66/175 (38%) of the parents had open questions mainly concerning the prognosis of the disease. Sources of information that were used after the consultation were most often the treating physician (150/175, 86%) and the internet (133/175, 76%).Conclusion Generally, parents perceive the initial medical consultation on the developmental disorder of their child well. Nevertheless, many parents state that they had unanswered questions after the consultation. The internet is one of the main sources parents use to answer those questions.
Keywords: developmental disorder; children; parents; initial medical consultation